Effects of Preoperative Mean Platelet Volume on Early Outcomes of Patients after Conventional Coronary Artery Bypass Graft Surgery (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: The Mean Platelet Volume (MPV) is a marker of platelet size with increased platelet activation. An elevated MPV is associated with major cardiac adverse events after Coronary Artery Bypass Graft (CABG) surgery. Effect of preoperative MPV on outcome of in-hospital patients after coronary artery bypass graft surgery was investigated in this study.Objective: To investigate the association of preoperative MPV with in-hospital outcome of patients after CABG surgery.Materials and Methods: An observational prospective study was carried out in the Department of Cardiovascular Surgery, National Institute of Cardiovascular Diseases (NICVD), Dhaka during the period from July 2012 to June 2014. Preoperative mean platelet volume was obtained prospectively in 81 consecutive patients undergoing conventional coronary artery bypass surgery. The patients were divided into two groups according to normal and elevated MPV at 10.60 femtolitre (fL) cut off level. Postoperative mortality and major adverse events were recorded in the early postoperative period.Results: Combined adverse events including post operative Myocardial Infarction (MI), arrhythmia, bleeding and death occurred in 27 patients (33.3%) during the early follow-up. The preoperative mean platelet volume levels were found to be associated with postoperative adverse events (p